Studi tentang Pengaruh Strategi Pengembangan SDM terhadap Ketahanan Organisasi: Inovasi dan Pengalaman Praktik Mahasiswa sebagai Variabel Mediasi - Sahabuddin, Romansyah; Riana, Eva; Aprilia, Rizky; Mustafa, Zhahra Nurazifa; Arif, Hery Maulana (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research aims to explore the influence of human resource (HR) development strategies on organizational resilience in facing crises through student practice experiences. In an increasingly dynamic and challenging context, this research examines how student involvement in work practices can make a significant contribution to innovation, flexibility and talent development in organizations. Quantitative techniques were used to conduct this research. The non-probability sampling approach is the sampling methodology used in this research with a sample size of 100 respondents, namely FEB UNM Management students. Partial least squares structural equation modeling (PLS-SEM) analysis is the data analysis method used. The results of this research prove that there is a positive direct influence between HR development strategies on organizational resilience, as well as indirect influences through work innovation variables and student practical experience.